Clinical Narrative Thinking and Its Value in Medical Practice - Xiaolin YANG; Jie SHEN (Yixue yu zhexue, 2025)
Clinical narrative thinking is a thinking mode equally significant as evidence-based thinking in clinical practice. It encompasses narrative patient education/disease popularization thinking, narrative diagnostic thinking, narrative decision-making thinking, and narrative care/intervention thinking. Based on the discourse system of "Chinese narrative medicine", this article proposes the definition of "clinical narrative thinking" and elaborates on the dialectical complementary relationship between narrative thinking and evidence-based thinking, expounds the similarities and differences between clinical narrative thinking and other thinkings, and explains the value of clinical narrative thinking in medical practice from three dimensions, namely, patient education before medical diagnosis and treatment, collaborative decision-making in medical diagnosis, and holistic health regulation during treatment. This article calls on more medical institutions to pay attention to the cultivation of narrative talents and the narrative thinking of clinicians.